Administrasi Pengelolaan Zakat Dalam Pemberdayaan Umat - Ii Sumantri (Department of Public Administration, 2020)
Even though the term zakat has been widely known by the people of Indonesia with the largest Muslim population in the world, awareness of paying zakat seems to be not optimal. This is suspected by the problem of the administrator and the management, namely that in practice there are two attitudes of the zakat payer himself. This study aims to analyze the administration of zakat management in empowering the people. In conducting this research, a qualitative approach was used with this type of descriptive research. The results of this study indicate that there are at least three ways to improve the professional administration of zakat management so that it can have an impact on empowering people more optimally. This research can be concluded that the actual economic weakness of the Ummah lies not in the absence of potential, but the weakness in processing the economic potential towards being productive and also in processing the economic potential of the Muslim community, not having no Islamic institution, but the existing institutions have not yet been fully trusted.